Isostatic state of the Upper Rhine graben - Miranda, Silvia (1998)
In any particular region isostatic anomalies point out the balance degree, establishing the excess or deficit of compensating masses. Nevertheless the distribution of these masses is not unique. Current isostatic models consider a simple dipolar mass configuration. The performance of predictive isostatic anomaly derived from an extensional crustal model, compensated in the Airy’s system, is analyzed for a sedimentary basin with intracrustal anomalous masses, settled on an anomalous lithospheric mantle. The gravimetric analysis for two cross sections of the Upper Rhine graben, is based on all the geophysical information available for this region: seismic results (reflection and refraction) and a remarkable thermal anomaly derived from several geophysical studies. The calculated isostatic anomalies and predictive vertical movements indicate: i- that nowadays the state is close to the isostatic balance both at north and south of the Rhine graben; ii- the future vanishing of the thermal anomaly in the southern section will cause thermal subsidence; iii- in qualitative terms, simple dipolar isostatic models are adequate for the predictive vertical movability evaluations.